Optimizing pathological assessment of breast cancer in Brazil: recommendations from a multidisciplinary working group on the tumor-tissue journey - Helenice Gobbi; Filomena Marino Carvalho; Rosemar Macedo Sousa Rahal; Maria Ines Klôh; Dimitrius Leonardo Pitol (Surgical and Experimental Pathology, 2022)
Abstract Timely and correct assessment of histopathological, immunohistochemical and molecular features of biopsy and surgical specimens is of paramount importance in the provision of care to patients with breast cancer, particularly in the current era of precision oncology. In order to ensure that tissue samples are obtained, processed, analyzed and reported in an optimal way, a concerted effort is required by institutions and individuals, taking into account state-of-the-art scientific and technical knowledge and circumventing logistic and operational constraints. This may be particularly challenging in some settings due to several sources of economic, structural, organizational and communication inefficiencies. In the current article, we present a brief review of breast cancer epidemiology and challenges in the disease diagnosis, especially in Brazil, and report the results of a multidisciplinary working group convened in May 2020 in an expert panel to identify and discuss the barriers and challenges related to the journey of breast cancer samples in Brazil. Following the identification of the issues, the working group also discussed and proposed recommendations for improving the journey and quality of breast cancer samples based on their professional experience and the current scientific literature, including guidelines of national and international health organizations (e.g. World Health Organization), consensus of medical societies and other published literature on the topic. We outline the most salient issues related to that journey in Brazilian public and private medical institutions, based on the experts’ clinical experience, since all of them are actively working at both sectors, and discuss current recommendations to address these issues aiming at mitigating and preventing preanalytical and analytical issues affecting diagnostic and therapeutic decisions. Such issues are grouped under four headings pertaining to education, communication, procedures in the operating room and sample transportation, and procedures in the pathology laboratory. Selected recommendations based on the current literature and discussed by the group of Brazilian experts are reviewed, which may mitigate the issues identified and optimize diagnostic and therapeutic decisions for patients with breast cancer, currently the most frequent malignant tumor worldwide and in Brazil. This paper has been submitted and published jointly, upon invitation and consent, in both the Surgical and Experimental Pathology and the Mastology journals.